فقہ السیرۃالنبویۃفی التفاسیرالمعاصرۃ: Fiqh-Al- Seerah in Contemporary Exegeses - Ahmad Shakri (Seerat Studies, 2023)
This article elaborates relationship between Seerah and Quranic exegeses with special reference to some contemporary Tafsir literature . The study also throws light on juristic aspect of Seerah as well as the lessons learnt from the Seerah of the Holy Prophet S.A.W . One of its findings is that Seerah of Prophet Muhammad S.A.W. is a primary source of Quranic interpretation.